The impact of digital infrastructure on energy-environmental efficiency: empirical evidence from China - Sun, Xiangxiang (Frontiers in Energy Research, 2023)
Frontier studies have focused on the environmental performance of traditional infrastructure, but have generally neglected the effects and mechanisms of digital infrastructure on energy-environmental efficiency. This study attempts to use fixed effect models and mediating effect model based on panel data from 30 provinces in China from 2010 to 2017 to assess the impact of digital infrastructure on energy environmental efficiency and identify its mechanism. The non-radial directional distance function is used to measure energy environmental efficiency. The empirical results show that digital infrastructure promotes energy-environmental efficiency, which remains robust after a series of tests. Technological progress and energy industry advancement are the pathways through which digital infrastructure affects energy-environmental efficiency. Furthermore, we find that the positive effect of digital infrastructure on energy and environmental efficiency is significant in the east and where factor mismatch is high. Therefore, policymakers should develop digital technology and enact various environmental policies to effectively increase the construction of digital infrastructure, promote investment in technology research and development, accelerate the energy technology progress, and improve energy efficiency.